Comparison of reading interest on printed textbook and digital textbook on the second semester students of Bahasa and literature department of FKIP Mataram University: The Comparison of Reading Interest on Printed Textbook and Digital Textbook on The Second Semester Students of Bahasa and Literature Department of FKIP Mataram University - Wika Wahyuni; Baiq Wahidah; Marlinda Ramdhani (Jurnal Bastrindo, 2023)
Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya minat baca masyarakat Indonesia. Salah satu alasan rendahnya minat baca tersebut adalah keterbatasan bahan bacaan. Namun, seiring perkembangan teknologi, upaya untuk mengatasi keterbatasan bahan bacaan ini adalah dengan diadakannya bahan bacaan dalam bentuk digital. Penelitian ini bertujuan untuk mengetahui apakah keberadaan buku digital ini telah menggeser minat baca menggunakan buku cetak. Selain itu, penelitian ini juga membahas alasan pemilihan bentuk bacaan, genre bacaan yang diminati, dan teknik membaca yang digunakan. Penelitian ini merupakan penelitian kualitatif. Teknik pengumpulan data dilakukan dengan kuesioner dan wawancara. Data dianalisis dengan menggabungkan analisis isi kualitatif dan kuantitatif sederhana. Temuan utama penelitian ini adalah kemudahan akses buku digital tidak serta-merta menjadikan buku digital lebih diminati. Temuan-temuan lainnya yaitu kurangnya minat mahasiswa dalam membaca buku pelajaran, membaca intensif lebih sering dilakukan dibandingkan membaca ekstensif, serta alasan memilih buku digital antara lain yaitu a) lebih ekonomis karena tidak perlu membeli buku cetak yang harganya relatif mahal, b) lebih praktis dan mudah dibawa, c) ramah lingkungan karena memerlukan lembaran kertas, dan d) tampilan lebih menarik, sedangkan alasan memilih buku cetak antara lain karena a) membaca buku digital pada gadget membuat mata lelah b) tidak mudah terdistraksi , dan c) lebih personal karena merasa memiliki. Abstract: This research is conducted as the concern of th high interest on digital books that easily accessed as one of the attempt to overcome limited reading materials. Based on this issue, this research aims to; discover the comparison between printed and digital books ; the reason of preferred kind of literature, preferred genre of literature, and the reading techniques that mostly used. This case study used qualitative method as the research design.  Data collection techniques were carried out using questionnaires and interviews. Data were analyzed by combining simple qualitative and quantitative content analysis.  Data is presented in the form of a diagram containing numbers explained in descriptive text.  The results of the research show that there are several findings.  The main finding is that the ease of access to digital books does not necessarily make digital books more desirable.  Other findings are the lack of interest of students in reading textbooks (non-fiction), intensive reading is more often done than extensive reading, and the reasons for choosing digital books include; a) more economical because there is no need to buy printed books which are relatively expensive; b)  more practical and easy to carry; c) environmentally friendly because it requires sheets of paper; and d) the appearance is more attractive. Furthermore, the reasons for choosing printed books include; a) reading digital books on gadgets makes the eyes tired (the influence of cellphone light); b) not easily distracted (the presence of notifications on the device disrupts reading activities; and c) the personal sense of belonging, they personally own the book.